PREDIKSI RISIKO PASAR DAN KEUNTUNGAN DENGAN MODEL CAPM SEBAGAI DASAR PENGAMBILAN KEPUTUSAN BERINVESTASI PADA SAHAM JAKARTA ISLAMIC INDEX PERIODE TAHUN 2006 - 2008 - Waryani, Devi Ika (Jurnal Ekonomi Pembangunan, 2009)
There are three purposes in this research are to know stock beta belong to JII, to know beta as risk premi (Rm-Rf) intended by third market, to know the result CAPM model count as basic investment decision making Securitas on JII stock. The method used from this research is descriptive of kualitative it means the purpose of this research to describe situation from count result. From the result above show that CAPM model can prove beta as risk level positive improve and significance although less more 1 value, it means fluctuation stock more weak and lower concerning index market fluctuation. The result grouping criteria was got decision suggestion inclining aim to buy stock because on the prediction to buy that stock in cheap so chance to investor increase their stock